2021
DOI: 10.1016/j.bbrc.2020.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability of SARS-CoV-2 virus like particles degrades with temperature

Abstract: SARS-CoV-2 is a novel coronavirus which has caused the COVID-19 pandemic. Other known coronaviruses show a strong pattern of seasonality, with the infection cases in humans being more prominent in winter. Although several plausible origins of such seasonal variability have been proposed, its mechanism is unclear. SARS-CoV-2 is transmitted via airborne droplets ejected from the upper respiratory tract of the infected individuals. It has been reported that SARS-CoV-2 can remain infectious for hours on surfaces. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…In this manuscript, we show that SARS-CoV-2 VLPs can be efficiently produced in insect cells, which are generally considered as more robust and cost-effective producer cells than mammalian hosts. Previous studies report expression of SARS-CoV-2 VLPs in 293T and Vero cell lines ( Boson et al, 2020 ; Plescia et al, 2020 ; Swann et al, 2020 ; Xu et al, 2020 ; Sharma et al, 2021 ), and one recent study in insect cells ( Mi et al, 2021 ); however, the authors do not specify the yield. It has to be noted that the glycosylation pattern of proteins expressed in insect cells differs from that of the native form produced in human cells, which is important for viral surface glycoproteins, as they play important roles in virus–host recognition and immune recognition and evasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manuscript, we show that SARS-CoV-2 VLPs can be efficiently produced in insect cells, which are generally considered as more robust and cost-effective producer cells than mammalian hosts. Previous studies report expression of SARS-CoV-2 VLPs in 293T and Vero cell lines ( Boson et al, 2020 ; Plescia et al, 2020 ; Swann et al, 2020 ; Xu et al, 2020 ; Sharma et al, 2021 ), and one recent study in insect cells ( Mi et al, 2021 ); however, the authors do not specify the yield. It has to be noted that the glycosylation pattern of proteins expressed in insect cells differs from that of the native form produced in human cells, which is important for viral surface glycoproteins, as they play important roles in virus–host recognition and immune recognition and evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, production of SARS-CoV-2 originating VLPs has been reported as well. Described particles can be divided into several subtypes, depending on the technology used: homotypic VLPs composed of coronaviral proteins only ( Boson et al, 2020 ; Lu et al, 2020 ; Plescia et al, 2020 ; Swann et al, 2020 ; Xu et al, 2020 ; Kumar et al, 2021 ; Sharma et al, 2021 ); heterotypic (chimeric) VLPs, where the SARS-CoV-2 S protein is incorporated into a heterologous viral scaffold (animal viruses or bacteriophages) ( Fougeroux et al, 2021 ; Roy et al, 2021 ; Tan et al, 2021 ); and heterotypic VLP where no coronaviral proteins are present, but fragments of coronaviral genetic material are encapsulated in either plant viruses or bacteriophages and may be used, for example, for diagnostic purposes ( Chan et al, 2021 ). Some authors also classify pseudoviruses displaying SARS-CoV-2 S protein as VLPs ( Ju et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diverse results, most studies concluded a negative correlation between temperature and COVID-19 transmission (McClymont & Hu 2021 , Paraskevis et al 2021 ). Laboratory research found that the structural stability of the SARS-CoV-2 virus quickly decreases at warm temperatures (Sharma et al 2021 ). It was believed that the incidence of COVID-19 can drop in the summertime.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cold and dry environments can have immunosuppressive effects on a potential host, further increasing the chances of infection [240][241][242]. Evidence suggests decreased transmission of SARS-CoV-2 in warmer climates [243][244][245][246], likely due to degeneration of viral structural stability with increasing temperatures [247]. Decreased transmission of SARS-CoV-2 was not observed during the summer of 2020 [11,248] likely because of the sheer number of cases and an immunologically naïve population.…”
Section: Multiple Factors Will Determine the Evolutionary Trajectory Of Sars-cov-2 And The Covid-19 Pandemicmentioning
confidence: 99%